2016
DOI: 10.1016/j.jpeds.2016.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Severity of Esophageal Acidification on Sleep vs Wake Periods in Infants Presenting with Brief Resolved Unexplained Events

Abstract: Objectives To describe the pattern of gastro-esophageal reflux (GER) events in wake and sleep states with increasing acid reflux index (ARI) in neonates and to test the hypothesis that GER-related symptoms are frequent in ARI> 7% in wake-state. Study design Infants underwent 24-hour pH-impedance studies with 6-hour concurrent video-polysomnography studies. Data were stratified based on the 24-hr ARI (% duration that esophageal pH is <4) into ARI<3% (normal), ARI 3≥ to ≤7% (intermediate) and ARI>7% (abnormal)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…MII-pH monitoring revealed acid or nonacid reflux in 2/3 of 53 HR-BRUE infants, non-acid reflux events were the most common findings (66%) (19) . A study performed in 25 infants presenting with BRUE who underwent concurrent MII-pH and video-polysomnography showed severe esophageal acid exposure (RI>7%) is associated with increased reflux-associated symptoms in wake state (20) .…”
Section: Discussionmentioning
confidence: 99%
“…MII-pH monitoring revealed acid or nonacid reflux in 2/3 of 53 HR-BRUE infants, non-acid reflux events were the most common findings (66%) (19) . A study performed in 25 infants presenting with BRUE who underwent concurrent MII-pH and video-polysomnography showed severe esophageal acid exposure (RI>7%) is associated with increased reflux-associated symptoms in wake state (20) .…”
Section: Discussionmentioning
confidence: 99%
“…The theory that GER events may play a causative role in CR events in infants is based on the existence of chemoreceptors in the upper airway able to elicit apnea to protect the airway, function influenced also by sleep/wake state, and on the existence of neuroreceptors responding to esophageal distension with vagal stimulation . Numerous studies have been published on the relationship between CR and GER events in infants, and on the nature of this relationship, but these studies have reported conflicting results .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changes in sleep patterns and interventions in NICU infants may modify the symptoms and responses to reflux events. [13,14] In an attempt to determine the burden of GERD, we studied 33 academic freestanding children's hospital NICUs in the United States. Using the definition of GERD based on symptoms, we noted a 13-fold variation (2% to 26%) in the diagnosis of GERD and found that infants with a diagnosis of GERD stayed 1 month longer in the NICU.…”
Section: Epidemiology and Burdenmentioning
confidence: 99%